(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Narayan, popularly known as R.K. Rashipuram Krishna swami. Narayan, born in Madras, India in 1906 died in 2001, Madras. Narayan is now considered to be one of English’s greatest Indian authors. He is the most creative of Indian authors, his sole purpose being to provide aesthetic pleasure, and not to use his art as a tool to serve any social purpose. In both high school and intermediate tests, he failed. When he was twenty-four years old, he could not get his degree. Such school and college setbacks make him shy, quiet and tentative, and introvert rather than extrovert. Ever since he has been reserved modest, rather too modest.